FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN: KEBIJAKAN DIVIDEN SEBAGAI PEMEDIASI - AULIA NUR HASANAH; WIDYAWATI LEKOK (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to get emperical evidence about the influence of managerial ownership, financial leverage, profitability, firm size, investment opportunity, dividend policy, cash holdings, and number of independence board to the firm value; The influence of managerial ownership, financial leverage, profitability, firm size, and investment opportuinity to the firm value which is mediated by dividend policy. The population are non financial companies listed in Indonesia Stock Exchange (IDX) from the period of 2014 to 2016. This study used 55 samples and samples selection procedure used purposive sampling. Data were analyzed using multiple regression method and path analysis. The result of this study shows that financial leverage, profitability, and dividend policy have influence toward firm value. While managerial ownership, firm size, investment opportunity, cash holdings and independence board have no influence toward firm value. Dividend policy mediate the correlation of managerial ownership and firm size to the firm value. While dividend policy does not mediate financial leverage, profitability, and investment opportunity to the firm value.